Abnormal returns to a fundamental analysis strategy. - Abarbanell, Jeffery S.; Bushee, Brian J. (The Accounting Review, 1998)
We examine whether the application of fundamental analysis can yield significant abnormal returns. Using a collection of signals that reflect traditional rules of fundamental analysis related to contemporaneous changes in inventories, accounts receivables, gross margins, selling expenses, capital expenditures, effective tax rates, inventory methods, audit qualifications, and labor force sales productivity, we form portfolios that earn an average 12- month cumulative size-adjusted abnormal return of 13.2 percent. We find evidence that the fundamental signals provide information about future returns that is associated with future earnings news. Moreover, a significant portion of the abnormal returns is generated around subsequent earnings announcements. These findings are consistent with the underlying focus of fundamental analysis on the prediction of earnings. Significant abnormal returns to the fundamental strategy are not earned after the end of one year of return cumulation, indicating little support for the idea that the signals capture information about multiple-year-ahead earnings not immediately impounded in price or about long-term shifts in firm risk. Additional analysis on a holdout sample suggests that the strategy continues to generate abnormal returns in a period subsequent to the introduction of the fundamental signals in the literature, and contextual analyses indicate that the strategy performs better for certain types of firms (e.g., firms with prior bad news).